Land Suitability and Availability Evaluation for Social Forestry in Pesawaran Regency, Lampung Province - Koeswara, Dieta Arbaranny; Widiatmaka; Suharjito, Didik (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
The Indonesian government established Social Forestry (SF) Program in 2015 to overcome inequality in land tenure, overcome agrarian conflicts and improve the welfare of communities around the forests. Pesawaran Regency does not yet have SF location guidelines in the Indicative and Social Forestry Areas Map. In fact, Pesawaran Regency has a forest area potential of 28% and has a Human Development Index (HDI) score below the provincial HDI average. This study aims to (1) analyze land use and cover changes in forest areas in 2015 and 2020, and (2) determine land potential for SF. SPOT image is used to analyze land cover with visual interpretation. Land suitability evaluation uses the Multi Criteria Evaluation (MCE) method based on Geographic Information Systems (GIS). The parameters used in this study were land/use cover, soil type, altitude, slope, rainfall, distance from rivers, distance from settlements, and distance from roads The results show that almost half of the forest area in 2020 is in the form of mixed gardens (49.63%), forests (24%), and coffee/cocoa plantations (22.2%). The potential land use changes are from forests to mixed gardens, coffee/cocoa plantation and mines. The parameters most influencing the land suitability for SF are land cover, slope, and soil type. Based on land suitability and land availability analysis for SF, it was found that 66% of the research area had potential for SF.